1996
DOI: 10.1016/s0741-5214(96)70008-3
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of air plethysmography and color-flow–assisted duplex scanning in the quantification of chronic venous insufficiency

Abstract: Limb reflux time as determined by color-flow-assisted duplex scans correlated significantly with the air plethysmographic variable accepted as a measure of the severity of venous reflux, the venous filling index. This study confirms the validity of total limb reflux times in the quantification of chronic venous insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
2
27
1
5
Order By: Relevance
“…Wu and co-workers used the duration of retrograde flow as a criterion for the quantification of jugular valve insufficiency [21]. In studies with a focus on peripheral veins, a significant correlation was detected between total valve closure time and reflux volume determined by an air plethysmography-derived venous filling index [14,20]. By analogy to these results obtained by studies on peripheral veins, our results suggest the presence of more severe valvular insufficiency in the patients with a reported trigger event.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and co-workers used the duration of retrograde flow as a criterion for the quantification of jugular valve insufficiency [21]. In studies with a focus on peripheral veins, a significant correlation was detected between total valve closure time and reflux volume determined by an air plethysmography-derived venous filling index [14,20]. By analogy to these results obtained by studies on peripheral veins, our results suggest the presence of more severe valvular insufficiency in the patients with a reported trigger event.…”
Section: Discussionmentioning
confidence: 99%
“…162 Venous plethysmography (strain-gauge, air, or photoplethysmography) provides additional venous limb physiologic parameters regarding global venous reflux, outflow obstruction, and calf muscle pump function and has shown good correlation with venous duplex ultrasound. [163][164][165][166][167][168] Some studies have shown utility for monitoring of venous functional changes and assessment of physiologic outcome of surgical treatments. [169][170][171][172] However, current evidence does not support a primary role for venous plethysmography as a diagnostic test for venous disease above venous duplex ultrasound.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…According to this concept we have generally used in our patients. The goal of compression therapy is to provide a gradient of pressure from the ankle to the knee or thigh, depending on the [27]. The disadvantages associated with stockings include the patient's difficulty in putting them on, especially over bandages like our patients.…”
Section: Discussionmentioning
confidence: 99%